Internalisasi Pendidikan Karakter Melalui Program Imtaq di SD Islam Ulil Albab Kebumen - Ifti Mukaromah; Sudadi Sudadi; Atim Rinawati (IAINU Kebumen, 2023)
The research objectives are to find out how the process of internalizing character education through the Imtaq program at Islamic Elementary School Ulil Albab Kebumen. This study uses a qualitative method, with data collection techniques of observation, interviews and documentation. Subject in this research namely: the principal, waka for student affairs, PAI teachers, homeroom teachers for class IV, and the head of TPQ. Data analysis techniques in This research uses Milles and Huberman model analysis techniques, namely: data collection, data reduction, data presentation and verification. The results of this study indicate that the internalization of character education through the Imtaq program at SD Islam Ulil Albab Kebumen uses three stages, namely value transformation, value transactions and transinternalization. At the transinternalization stage, it is applied in the form of the Imtaq program. The forms of the Imtaq program carried out were praying before and after studying, reading Asmaul Husna, Duha prayer, Zuhur prayer in congregation, Koran program, Hadith memorization, Infaq habituation and Ramadan practice. This activity aims so that students are able to understand, appreciate, and can practice religious values ​​so that later they become students' characters. The internalized character values ​​of the Imtaq program are: religious values, honesty, discipline, hard work, responsibility and social care.